Study the effect of Camellia sinensis alcoholic extract against Gram negative bacteria isolated from eye infections ( conjunctivitis) - Sundus Adil Naji (مجلة بغداد للعلوم)
The present study examined the effect of alcoholic extract of Camellia sinensis against Gram negative bacteria isolated from eyes infections (conjunctivitis), 25 specimens (39.68%) gave positive bacterial culture from a total of 63 samples. The bacteria detected includes Pseudomonas aeruginosa  (12.69%), Enterobacter spp. (7.93%), Escherichia coli (6.34%), Moraxella spp. (4.76%), Proteus mirabilis (4.76%) and Klebsiella spp. (3.17%).